The system of investment and construction project management as a component of the company’s sustainable development - O. E. Astafyeva; S. V. Sianin (Вестник университета)
Investment and construction companies that have adopted the principles of sustainable development need to transform the project management system accordingly. The article discusses the integration of sustainable development in the management system of investment and construction projects. For this purpose, an analysis of scientific works in this area was conducted. During the study, the correspondence of adaptive management to the concept of sustainable development was revealed. As a result, the certain project management tools (Impact Map, management tasks assignment matrix / RACI (responsible, accountable, consult, inform), kanban board, DMAIC concept (define, measure, analyse, improve, control), Lean Six Sigma, business model canvas for sustainability) were compared with the mechanisms for integration of sustainable development (the definition of sustainable development activities, commitment action log, acceptance (consideration) of complaints, the improvement of sustainable development implementation in investment and construction projects and determination of sustainable development results in reporting). As a result, the problems of accounting and tracing at all stages of sustainable development requirements, as well as the problems of formation of correspondence reporting, were solved.